The Antecedents of Purchasing Intention on Electric Vehicles in Indonesia - Hendardi Agustino Gondoiswanto; Liliana Inggrit Wijaya (AMAR (Andalas Management Review), 2023)
The purpose of this study is to find out what is the attraction or that makes people in Indonesia interested in buying electric vehicles. In this study using several variables, namely feelings of environmental responsibility, environmental values, environmental knowledge, perceptions of environmental advertising, perceptions of electric vehicles, and the intention of purchasing electric vehicles. This research is basic research and uses quantitative methods. The correlation and regression matrices used are then processed with the stages of measurement model and structural model. Respondents were obtained by distributing questionnaires to as many as 300 respondents who understood electric vehicles and / or environmental issues. The results showed significant results except for environmental knowledge and perceptions of environmental advertising on electric vehicles. Advertisements in circulation are still few and not affected by environmental knowledge so that purchase intentions cannot be encouraged through this.